In vitro induction of the ubiquitous 60 and 70KD heat shock proteins by pesticides monocrotophos and endosulphan in Musca domestica: potential biomarkers of toxicity - Rohilla, M. S.; Reddy, P. V. J.; Sharma, S.; Tiwari, P. K. (Cellular and Molecular Biology, 2011)
This study has investigated the effect of two highly toxic pesticides, monocrotophos (organophosphate) and endosulphan (organochlorine), on the inducibility of two major heat shock proteins, the HSP60 and HSP70, essential for cell survival, in the house fly Musca domestica. The LC50 values of the two pesticides for larva and adult (monocrotophos: 0.05 ppm for larva and 0.025 ppm for adult; endosulphan: 15 ppm for larva and 2 ppm for adult) revealed monocrotophos to be potentially more toxic than endosulphan. The relative susceptibility (lethality) of adult to either of these pesticides appeared much higher than that of larva. The expression patterns of HSP60 and HSP70 were analysed in various larval and adult tissues, exposed to varying sub-acute doses of monocrotophos (0.00010 ppm - 0.00075 ppm for larva and 0.00010 ppm – 0.00050 ppm for adult) and endosulphan (0.5ppm – 2.0ppm for larva and 0.01ppm-0.10 ppm for adult). The immunoblots revealed significant correlation between the pattern of HSP’s expression and the pesticides-induced tissue injury/ mortality, visualized by trypan blue dye exclusion test. Both the pesticides caused significant induction of these HSPs in a tissue and dose-dependent manner, suggesting their importance as molecular indicators (biomarker) in the assessment of cellular toxicity caused by endosulphan and monocrotophos.